Association of variants in NEDD4L with blood pressure response and adverse cardiovascular outcomes in hypertensive patients treated with thiazide diuretics - McDonough, Caitrin W. (2013)
OBJECTIVE: Single-nucleotide polymorphisms (SNPs) in NEDD4L may influence the ability of the NEDD4L protein to reduce epithelial sodium channel expression. A variant in NEDD4L, rs4149601, was associated with antihypertensive response and cardiovascular outcomes during treatment with thiazide diuretics and β-blockers in a Swedish population. We sought to further evaluate associations between NEDD4L polymorphisms, blood pressure response and cardiovascular outcomes with thiazide diuretics and β-blockers. METHODS: Four SNPs, rs4149601, rs292449, rs1008899 and rs75982813, were genotyped in 767 patients from the Pharmacogenomic Evaluation of Antihypertensive Responses (PEAR) clinical trial and association was assessed with blood pressure response to hydrochlorothiazide and atenolol. One SNP, rs4149601, was also genotyped in 1345 patients from the International Verapmil SR Trandolapril Study (INVEST), and association was examined with adverse cardiovascular outcomes relative to hydrochlorothiazide treatment. RESULTS: Significant associations or trends were found between rs4149601, rs292449, rs75982813 and rs1008899 and decreases in blood pressure in whites on hydrochlorothiazide, and a significant association was observed with increasing copies of the GC rs4149601-rs292449 haplotype and greater blood pressure response to hydrochlorothiazide in whites (P = 0.0006 and 0.006, SBP and DBP, respectively). Significant associations were also seen with rs4149601 and an increased risk for adverse cardiovascular outcomes in whites not treated with hydrochlorothiazide [P = 0.022, odds ratio (95% confidence interval) = 10.65 (1.18–96.25)]. CONCLUSION: NEDD4L rs4149601, rs292449 and rs75982813 may be predictors for blood pressure response to hydrochlorothiazide in whites, and NEDD4L rs4149601 may be a predictor for adverse cardiovascular outcomes in whites not treated with hydrochlorothiazide.